Simulasi Sistem Pengaturan Kecepatan Mobil Menggunakan Pengendali PID (Proportional- Integral- Derivative) - Iksal, Iksal (Teknologi Nusantara, 2023)
Along with development Knowledge and Technology ,, especially in development industry as well as for help work human nature routine, use system control has Lots done man good for automation equipment industrial , office nor for needs control equipment house personal .. One of lots of controllers used in industry is PID ( Proportional-Integral – Derivative) controller . PID controller aim for repair response system , for example reduce or remove error steady state or enlarge speed response . In research this will controlled speed cars ,, esp for car wheeled four. Speed car need controlled for avoid speed car outside potential control happen accident moment drive . Based on characteristics from the object to be deeply controlled matter this speed car, then used PID controller because controller This based on the criteria very suitable used for control speed car . From the results the simulation done the following data were obtained : (1) Rise-Time (rising time) R s about 0.27 seconds from specifications provided < 5 seconds , (2) Maximum Over Shoot 5 % from specification Which has determined previously yeah < 10% , (3) Settling Time Ts= 2.71 second, and (4) Error Steady State 1% . Special for controller PID, value satisfying constant condition from the specifications given are K p = 0.026, K I = 0.5325 , and K D = 0.125, respectively. Based on variable response transient that, with thereby controlled system stable because fulfil even more good from specifications provided in planning